PENERAPAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MAKNA SILA-SILA PANCASILA KELAS IV SD - Prayitno, Edy; Labudasari, Erna; Nurningsih, Ade (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Abstract: Classroom Action Research is a research method conducted by teachers with the aim of improving the quality of learning. The study aimed to assess how much improvement students' learning outcomes or cognitive levels were. The data collection method used in this study is a test. The testing method was applied to collect information about the learning outcomes of grade IV students in Pancasila education lessons about the meaning of Pancasila precepts before, during, and after research. The increase in the completeness of students from pre-cycle action to cycle I action increased by 9 students. The action of cycle I to cycle II increased by 12 students (36.37%), so that in the action of cycle II students who experienced an increase in learning completeness which in cycle I the number of students who completed was 17 students (51.51%) increased to 29 students who completed (87.88%). Based on the research that has been conducted, it can be concluded that the application of the Culturally Responsive Teaching approach can improve the learning outcomes of students in Pancasila Education lessons on the Meaning of Pancasila Precepts. Keywords:Classroom Action Research, Culturally Responsive Teaching, Pancasila Education, The Meaning of Pancasila Precepts. Abstrak: Penelitian Tindakan Kelas yaitu sebuah metode penelitian yang dilakukan oleh guru dengan tujuan untuk memperbaiki kualitas pembelajaran. Studi ini bertujuan untuk menilai seberapa besar peningkatan hasil belajar siswa atau tingkat kognitif mereka. Metode pengumpulan data yang digunakan dalam penelitian ini adalah tes. Metode pengujian diterapkan untuk mengumpulkan informasi mengenai hasil belajar siswa kelas IV dalam pelajaran pendidikan pancasila tentang makna sila-sila Pancasila sebelum, selama, dan setelah penelitian. Peningkatan ketuntasan peserta didik dari tindakan pra siklus ke tindakan siklus I meningkat yakni sebanyak 9 siswa. Tindakan siklus I ke siklus II meningkat sebanyak 12 siswa (36,37%), sehingga pada tindakan siklus II siswa yang mengalami peningkatan ketuntasan belajar yang pada siklus I jumlah siswa yang tuntas adalah 17 siswa (51,51%) meningkat menjadi 29 siswa yang tuntas (87,88%).Berdasarkan penelitian yang telah dilakukan maka dapat disimpulkan bahwa penerapan pendekatan Culturally Responsive Teaching dapat meningkatkan hasil belajar siswa pelajaran Pendidikan Pancasila materi Makna Sila-Sila Pancasila. Kata Kunci: Penelitian Tindakan Kelas, Culturally Responsive Teaching, Pendidikan Pancasila, Makna Sila-Sila Pancasila.